Effects of Mindfulness-Based Interventions on Quality of Life Among Patients with Hypertension: A Systematic Review - Erika Dewi Noorratri; Martini Martini; Siti Fatimah Pradigdo; Suroto Suroto; Meidiana Dwidiyanti; Bagoes Widjanarko; Wahyuni Wahyuni (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2026)
Introduction: In modern healthcare when therapeutic approaches have advanced, hypertension remains a challenging long-term medical condition. A major cause of not only cardiovascular but also kidney disease is hypertension. Moreover, hypertension globally and significantly contributes to death rates, becoming a contributing factor to cardiovascular morbidity and mortality. Dealing with chronic disease management, hypertension is truly challenging as patients have uncontrolled blood pressure. This threatens physical health as well as patients’ quality of life (QoL). Thus, enhancing hypertensive patients’ well-being through interventions is important. Mindfulness-based interventions (MBIs) is a potential non-pharmacological approach to improve hypertensive patients’ QoL. Objective: To assess MBIs impacts on hypertensive patients’ QoL. Method: This study employed a systematic review methodology following by PRISMA 2020 guidelines. Scopus, ScienceDirect, also ProQuest were the selected databases, including articles published between 2020 and 2024. Referring to the predefined criteria, a screening process was structurally conducted to select the studies. The inclusion criteria focused on MBIs in hypertension, resulting in 8 eligible studies. Results: The findings show that MBIs positively impact the hypertensive patients’ QoL, indicating improvements in QoL and other related outcomes. Heterogeneity dealing with study design and outcome measure exists within the selected studies though. Not all studies directly assessed QoL, with some relying on indirect indicators. Conclusion: The potential of MBIs is significant, serving as a complementary non-pharmacological strategy to promote hypertensive patients’ QoL. Thus, healthcare providers are expected to apply mindfulness approaches into the holistic management of hypertensive individuals.